Chinese radicals in spaced repetition systems : a pilot study on the acquisition of Chinese characters by students learning Chinese as a foreign language - De la Rouviere, Jeremiah Daneil (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.